A Brief Comment on Nora Jaffary’s Reproduction and Its Discontents - Hernández Sáenz, Luz (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2018)
This article offers a brief commentary on Reproduction and Its Discontents by Nora Jaffary. It includes a short summary and analysis of the work’s main points, with an emphasis on the section on monstrous births and its historical context.